Multiplicity in polyp count and extracolonic manifestations in 40 Dutch patients with MYH associated polyposis coli (MAP). Issue 9 (1st September 2005) - Nielsen, M; Franken, P F; Reinards, T H C M; Weiss, M M; Wagner, A; van der Klift, H; Kloosterman, S; Houwing-Duistermaat, J J; Aalfs, C M; Ausems, M G E M; Bröcker-Vriends, A H J T; Gomez Garcia, E B; et al.
Abstract : Objective: To investigate the contribution of MYH associated polyposis coli (MAP) among polyposis families in the Netherlands, and the prevalence of colonic and extracolonic manifestations in MAP patients. Methods: 170 patients with polyposis coli, who previously tested negative for APC mutations, were screened by denaturing gradient gel electrophoresis and direct sequencing to identify MYH germline mutations. Results: Homozygous and compound heterozygous MYH mutations were identified in 40 patients (24%). No difference was found in the percentage of biallelic mutation carriers between patients with 10–99 polyps or 100–1000 polyps (29% in both groups). Colorectal cancer was found in 26 of the 40 patients with MAP (65%) within the age range 21 to 67 years (median 45). Complete endoscopic reports were available for 16 MAP patients and revealed five cases with gastro-duodenal polyps (31%), one of whom also presented with a duodenal carcinoma. Breast cancer occurred in 18% of female MAP patients, significantly more than expected from national statistics (standardised morbidity ratio = 3.75). Conclusions: Polyp numbers in MAP patients were equally associated with the attenuated and classical polyposis coli phenotypes. Two thirds of the MAP patients had colorectal cancer, 95% of whom were older than 35 years, and one third of a subset of patients had upper gastrointestinal lesions. Endoscopic screening of the whole intestine should be carried out every two years for all MAP patients, starting from age 25–30 years. The frequent occurrence of additional extraintestinal manifestations, such as breast cancer among female MAP patients, should be thoroughly investigated.